2012
DOI: 10.1002/pits.21666
|View full text |Cite
|
Sign up to set email alerts
|

Extending Self‐management Strategies: The Use of a Classwide Approach

Abstract: Notwithstanding the wealth of research that documents the effectiveness of self‐management programs in the classroom, few investigations have explored classwide use of self‐management procedures as a universal intervention. To extend existing research in this area, we examined the effectiveness of a classwide self‐management intervention for decreasing disruptive behaviors among three at‐risk second‐grade students. We used a multiple baseline across subjects design and evaluated the effects of the self‐managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…Taken together, these findings suggest that students who engage in moderate levels of disruptive behaviors may respond to class-wide interventions more readily than students with more intense behavior needs. This further supports previous research in which students with higher behavioral needs respond slower to class-wide self-management interventions (e.g., Hoff & Ervin, 2013;Trevino-Maack, Kamps, & Wills, 2015). The reduction in disruptive behavior for three of the students during the final intervention condition seems to support this hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, these findings suggest that students who engage in moderate levels of disruptive behaviors may respond to class-wide interventions more readily than students with more intense behavior needs. This further supports previous research in which students with higher behavioral needs respond slower to class-wide self-management interventions (e.g., Hoff & Ervin, 2013;Trevino-Maack, Kamps, & Wills, 2015). The reduction in disruptive behavior for three of the students during the final intervention condition seems to support this hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Self-monitoring in this study showed similar effects to teacher monitoring, as did studies of Tiger et al (2009) and Hoff and Ervin (2013). Self-monitoring is an efficient technique that promotes generalization (Stokes & Baer, 1977).…”
Section: Discussionsupporting
confidence: 73%
“…In their critical review of the research on self-monitoring interventions, Webber, Scheuermann, McCall, and Coleman (1993) described how self-monitoring interventions could have potential benefits over teacher-monitoring interventions in special education classrooms, but at the time few studies had compared these approaches in special education environments. Hoff and Ervin (2013) implemented teacher-led interventions in classrooms and showed that disruptive behaviors decreased in three students. Although all three monitoring approaches increased student responding, teachers' responses to a questionnaire indicated that peer-monitoring and self-monitoring strategies were easier to implement, demonstrating that interventions that focus on self-monitoring can potentially decrease teachers' workloads.…”
Section: Self-monitoring Interventionsmentioning
confidence: 99%
“…Two SSD studies applying an antecedent-based [ 50 ] and a self-regulation intervention [ 51 ] produced effect sizes of 1.96 and 2.53, respectively. For the other two SSD studies applying a consequence-based and a self-regulation intervention, mean class’ disruptive behavior decreased on average with 52% and 36% respectively during intervention phases as compared to baseline phases [ 52 ].…”
Section: Resultsmentioning
confidence: 99%